A versatile CeO2/Co3O4 coated mesh for food wastewater treatment: Simultaneous oil removal and UV catalysis of food additives. (15th June 2018) - Liu, Ya'nan; Liu, Na; Chen, Yuning; Zhang, Weifeng; Qu, Ruixiang; Zhang, Qingdong; Tzungyu-Shih,; Feng, Lin; Wei, Yen
Abstract: Food waste water is one of the most urgent environmental problems for the close connection between food and our daily life. Herein, we use a simple hydrothermal method to prepare a highly efficient catalyst—CeO2 /Co3 O4 compound on the stainless steel mesh, aiming for food waste water treatment. Possessing the superhydrophilic property and catalytic ability under ultraviolet light, CeO2 /Co3 O4 coated mesh has successfully processed three representative contaminants in food wastewater, which are soybean oil (food oil), AR (food dye) and VA (food flavor) simultaneously with an one-step filtration. Besides, the mesh is stable in a wide pH range and performs well in reusability. Therefore, such a multifunctional material with simple preparation method, high processing efficiency and facile operation shows a promising prospect for practical production and application for food wastewater treatment. Graphical abstract: Highlights: A facile and effective strategy for removing multiclass pollutants from food wastewater simultaneously. A novel CeO2 /Co3 O4 decorated mesh possesses both special wettability and photocatalytic abilities. Dopamine was used to increase the amounts of CeO2 /Co3 O4 composites on the mesh for improved performances. Stability in a wide pH and good reusability provide mesh potential application for practical food wasterwater treatment.